A Review of the Existing Advance of Photovoltaic Thermal Air Collector: Drawbacks and Future Development - Maysara Talal; Ali Ismaeel; Iman Kareem (Journal of Renewable Energy and Environment)
This research highlights the pressing need of transitioning from fossil fuels to renewable energy due to resource depletion, supply instability, and climate change. It specifically focuses on the significance of solar energy both environmentally and economically, emphasizing its role in reducing carbon emissions and preserving the environment. This comprehensive review surveys and analyzes existing and advanced photovoltaic-thermal (PVT) models. The survey includes the fundamentals of photovoltaic cell operation and its impact, solar collector integration with photovoltaic systems, PVT cooling strategies, and performance indicators. In addition, the importance of energy storage technologies in managing fluctuations in renewable energy generation is emphasized, underscoring the need for sustainability in this transition. The central aim of the current study is to summarize practical and theoretical research, identify strengths and weaknesses, and propose future directions for the development of photovoltaic-thermal systems.